A Dumbbell Shaped Piezoelectric Motor Driven by the First-Order Torsional and the First-Order Flexural Vibrations - Jianye Niu; Jiang Wu; Qiming Liu; Li Chen; Shijie Guo (Actuators, 2020)
A piezoelectric motor driven by the first-order torsional and first-order flexural (T/F) vibrations is designed, fabricated, and tested in this study. The actuating force is generated by the torsional vibration of the dumbbell-shaped vibrator, while the elliptical motion shape is adjusted with the flexural vibration. The rotor, pressed onto the vibrator’s lateral surface, is frictionally driven with the vibrator. Here, the torsional vibration, the shear modes of piezoelectric ceramics, and the driving method may contribute to high torque and high output power. To test the feasibility of our proposal, first, a prototype of the T/F vibrator is built and its vibration properties are explored. As predicted, the torsional and flexural vibrations are excited on the vibrator. Then, the load characteristics of the piezoelectric motor are investigated. The maximal torque, the no-load rotation speed, and maximal output power are 4.3 Nm, 125 r/min, and 16.9 W, respectively. The results imply that using the first-order torsional and the first-order flexural vibrations is a feasible method to achieve high torque and high output power of piezoelectric motors.